2020
DOI: 10.3390/antibiotics9070409
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of Thymol and Carvacrol Contents Reveals the Level of Antibacterial Activity of the Essential Oils from Different Accessions of Oliveria decumbens

Abstract: Oliveria decumbens (Apiaceae) is an aromatic herb traditionally employed in the Persian medicine for the treatment of infectious and gastrointestinal disorders. In the present study, we analyzed the chemical composition of essential oils obtained from different Iranian populations and evaluated their efficacy on a panel of human pathogens (Staphylococcus aureus and Escherichia coli), probiotic (Bacillus subtilis), and phytopathogens (Clavibacter michiganensis, Curtobacterium flaccumfaciens, Xanthomonas citri, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
1
13
1
Order By: Relevance
“…The MIC of carvacrol oil for the tested Staphylococcus isolates was 0.04%, as observed for a variety of microorganisms [50][51][52][53][54]. In addition, carvacrol was suggested as the bioactive compounds against S. aureus and other Gram-positive and Gram-negative bacteria [51]. Moreover, de Souza et al [53] evaluated the antimicrobial potential of carvacrol in vitro and in vivo in Swiss mice against MDR K. pneumoniae strains and indicated that the use of carvacrol as a therapeutic agent can exert significant in vitro and in vivo antimicrobial effects against carbapenemase-producing K. pneumoniae (KPC), increasing animal survival and significantly decreasing bacterial loads; such preliminary results in mice were hopeful and indicated that carvacrol has potential as an antimicrobial agent.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The MIC of carvacrol oil for the tested Staphylococcus isolates was 0.04%, as observed for a variety of microorganisms [50][51][52][53][54]. In addition, carvacrol was suggested as the bioactive compounds against S. aureus and other Gram-positive and Gram-negative bacteria [51]. Moreover, de Souza et al [53] evaluated the antimicrobial potential of carvacrol in vitro and in vivo in Swiss mice against MDR K. pneumoniae strains and indicated that the use of carvacrol as a therapeutic agent can exert significant in vitro and in vivo antimicrobial effects against carbapenemase-producing K. pneumoniae (KPC), increasing animal survival and significantly decreasing bacterial loads; such preliminary results in mice were hopeful and indicated that carvacrol has potential as an antimicrobial agent.…”
Section: Discussionsupporting
confidence: 69%
“…Carvacrol is a significant component of essential oils and has recently attracted much attention as a result of its biological properties including a wide spectrum of antimicrobial activity [50]. The MIC of carvacrol oil for the tested Staphylococcus isolates was 0.04%, as observed for a variety of microorganisms [50][51][52][53][54]. In addition, carvacrol was suggested as the bioactive compounds against S. aureus and other Gram-positive and Gram-negative bacteria [51].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Mostly collected from the >2500 m heights from the skirts of central Zagros mountains in Fars, Chaharmahal & Bakhtiari, Kohgilouyeh & Boyerahmad, Boushehr, and Khuzestan provinces. The top chemical compounds have been reported in the plant including thymol, carvacrol, gamma-terpinene, and para-cymene ( Khoshbakht et al, 2020 ). Each one of them has significant chemotherapeutic agent potential and also antibacterial properties ( Ashraf, 2020 ; Ashraf et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on the determination of the antibacterial activity of EOs and PEs in vitro against Psg [ 6 ], Cff [ 34 , 35 ], and both bacteria simultaneously [ 36 , 37 ]. A single in vivo study of the control of Psg soybean seed infection has been reported [ 38 ], while no experiments on Cff infection in soybean have been performed to date.…”
Section: Introductionmentioning
confidence: 99%